Let's get to know each other [student workbook on the culture, heritage, origins and traditions of the] national minorities of Bosnia and Herzegovina - Valenta, Leonard (OSCE, 2009)
The Workbook is part of a wider effort entailing training sessions, workshops and lectures on national minorities, particularly on how to present this topic to the future of BiH society - children. It is designed to assist in lessons on the topic for primary school students. Yet moderators and teachers can also adapt it for use in secondary schools, training sessions, thematic workshops, etc. A methodological manual accompanies the Workbook, providing for creative applications to engage students or working group members. In school, the Workbook can be used in the teaching of History, Geography, Languages, Civic Classes, Ethics, Environmental Studies, Social Studies, or in extra-curricular activities and additional classes.